A review of in vitro attempts to develop the axenic culture of Treponema pallidum and genomics-based suggestions to achieve this elusive goal. Issue 7 (30th July 2021) - Belkacemi, Souad; Tidjani Alou, Maryam; Khelaifia, Saber; Raoult, Didier
Abstract : To date, the axenic culture of Treponema pallidum remains a challenge in the field of microbiology despite countless attempts. Here, we conducted a comprehensive bibliographic analysis using several databases and search engines, namely Pubmed, Google scholar, Google, Web of Science and Scopus. Numerous unsuccessful empiric studies have been conducted and evaluated using as criteria dark-field microscopic observation of motile spiral shaped cells in the culture and virulence of the culture through rabbit infectivity. All of these studies failed to induce rabbit infectivity, even when deemed positive after microscopic observation leading to the misnomer of avirulent T. pallidum . In fact, this criterion was improperly chosen because not all spiral shaped cells are T. pallidum . However, these studies led to the formulation of culture media particularly favourable to the growth of several species of Treponema, including Oral Microbiology and Immunology, Zürich medium (OMIZ), Oral Treponeme Enrichment Broth (OTEB) and T-Raoult, thus allowing the increase in the number of cultivable strains of Treponema . The predicted metabolic capacities of T. pallidum show limited metabolism, also exhibited by other non-cultured and pathogenic Treponema species, in contrast to cultured Treponema species. The advent of next generation sequencing represents a turning point in this field, as the knowledge inferred from the genome can finally lead to the axenic culture of T. pallidum .